The search for new parameters on evaluation of P300 potential - Korostenskaja, Milena; Dapšys, Kastytis; Mačiulis, Valentinas; Rukšėnas, Osvaldas (Psichologija, 2003)
ERPs could be helpful in the objectification of many psychological measures. One of the most commonly used ERPs in the last decades is P300 potential. It may be used in differentiation of cognitive dysfunction in patients suffering from schizophrenia, dementia, depression, and also could be successfully applied in treatment monitoring. Nevertheless, changes of P300 parameters (prolongation of latency or reduction of amplitude) are not highly specific for certain kinds of diagnosis. In this study we searched for more strict and specific P300 characteristics, which would be selective for different kinds of disorders. 86 healthy subjects were studied during the study. Ten new P300 measures were considered. Main results of the study are as follows: Overall six out of ten new considered measures had significant correlation with age: P3 energy (EP3), amplitude ratio (AS), latency and amplitude ratio (LAS), steepness of cognitive complex (KKKS), identification time (AT) and the global power of cognitive complex (KKTG). All these parameters could be considered to differentiate cognitive processing in general. From all studied parameters the best correlation with age demonstrated global power of cognitive complex (KKTG) and latency of P3 (L(P3)). Latency ratio (LS) is very stable parameter and therefore could be used in psychiatric diagnostic. The next step in search of selective P300 measures would be evaluation of effectiveness of the described P300 potential parameters in patients with schizophrenia, depression, dementia, epilepsy and other psychiatric disorders. For this purpose these parameters are considered: P3 energy (E(P3)), amplitude ratio (AS), latency and amplitude ratio (LAS), steepness of cognitive complex (KKKS), identification time (AT), latency of N2 (L(N2)), global power of cognitive complex (KKTG), latency of P3 (L(P3)) and latency ratio (LS).